ANALISIS YURIDIS TERHADAP PERUBAHAN MASA JABATAN KETUA KPK BERDASARKAN PUTUSAN MK RI Nomor: 112/PUU-XX/2022 - Karlina, Yunawati; Putra, Irwan Sapta (LPPM Universitas Bina Bangsa, 2024)
This research examines the legal rules related to the term of office of the chairman of the Corruption Eradication Commission (KPK)? And what is the impact of the Constitutional Court decision Number: 112/PUU-XX/2022 on the term of office of the KPK leadership. This research method is normative legal research with an analytical case study approach. Normative juridical analysis. The results of this study are FIRST The legal regulations related to the tenure of the KPK chairman are regulated in Article 34 of Law Number 30 of 2002 concerning the Corruption Eradication Commission (State Gazette of the Republic of Indonesia of 2002 Number 137, Supplement to the State Gazette of the Republic of Indonesia Number 4250) which reads: